Pengaruh Pendidikan Dan Kesehatan Terhadap Kemiskinan Di Kabupaten/ Kota Provinsi Aceh Tahun 2014-2017 - yuliana yuliana; Yulfrita Adamy; Edward M.Nur; Rita Zahara (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to analyze the effect of education and health on poverty in districts / cities of Aceh Province 2014-2017. The data used are secondary data in the form of time series data from 2015-2017 and cross section data of 23 districts / cities in Aceh Province. The data analysis technique used in this research is panel data regression, which is a combination of cross-section data with time series data. The data is processed using the software eviews 9. The model used in this study is as follows: Y = α + β1 + Pit + β2 Kit + it. The research results obtained from the fixed effect note that all variables are significant in the model, so that the Fixed Effect Model (FEM) estimation is obtained as follows: Y = 4.72 + 0.02Pit - 0.03Kit + 0.68eit where the constant value is 4.72 percent, it means that education and health towards poverty have a positive relationship of 4.72 percent. The value of the coefficient X1 = 0.02, meaning that the effect of education on poverty has a positive relationship of 0.02. It is interpreted that if the education variable has increased by 1%, there will be an increase of 0.02 percent of poverty. The coefficient value of X2 = -0.03, meaning that the health effect on poverty has a negative relationship of 0.03. It is interpreted that if the health variable has decreased by 1%, there will be a decrease of 0.03 percent towards poverty